Generalized anxiety related to Covid_19 in the residents of the Chaipé neighborhood of the city of Encarnación, year 2020 (Journal on studies and research of academic knowledge, 2021)
This research is called Generalized Anxiety related to COVID-19 in the inhabitants of Chaipé neighborhood of the city of Encarnación, year 2020. It has as its general objective: To analyze the symptoms associated with anxiety in the inhabitants of Chaipé neighborhood of Encarnación, during the quarantine of COVID-19, year 2020. Methodologically it is a descriptive research, with a mixed approach, whose study area was the Chaipé neighborhood of the city of Encarnación, in the department of Itapúa, composed of a population of 574 inhabitants. Questionnaire techniques were used in data collection. The most outstanding results showed that the residents of the Chaipé neighborhood go through a series of situations; economic, family and educational, which may or may not be aggravated by the current situation, which lead to mental health being affected causing a state of concern, which can increase with a high degree of anxiety and general somatic symptoms, therefore, It is necessary to have more professionals who take care of primary care and help manage emotions in this new situation that is experienced due to the COVID-19 pandemic.
Keywords: Psychology; Population; Mental health; COVID_19.